The Current Status of MOF and COF Applications - Freund, Ralph; Zaremba, Orysia; Arnauts, Giel; Ameloot, Rob; Skorupskii, Grigorii; Dincă, Mircea; Bavykina, Anastasiya; Gascon, Jorge; Ejsmont, Aleksander; Goscianska, Joanna; Kalmutzki, Markus; Lächelt, Ulrich; et al. (Angewandte Chemie International Edition, 2021)
The amalgamation of different disciplines is at the heart of reticular chemistry and has broadened the boundaries of chemistry by opening up an infinite space of chemical composition, structure, and material properties. Reticular design has enabled the precise prediction of crystalline framework structures, tunability of chemical composition, incorporation of various functionalities onto the framework backbone, and as a consequence, fine‐tuning of metal–organic framework (MOF) and covalent organic framework (COF) properties beyond that of any other material class. Leveraging the unique properties of reticular materials has resulted in significant advances from both a fundamental and an applied perspective. Here, we wish to review the milestones in MOF and COF research and give a critical view on progress in their real‐world applications. Finally, we briefly discuss the major challenges in the field that need to be addressed to pave the way for industrial applications. Leveraging the unique properties of reticular materials has resulted in significant advances from both a fundamental and an applied perspective. This Review reports on the milestones in MOF and COF research and gives a critical view on progress in their real‐world applications. The major challenges in the field that need to be addressed to pave the way for industrial applications are also discussed.